Reviews of recent publications (Studies in 20th & 21st Century Literature, 1997)
Culture and Theory Conley, Verena Andermatt, ed. Rethinking Technologies by Laurence M. Porter Leitch, Vincent B. Cultural Criticism, Literary Theory, Poststructuralism by Merry M. Pawlowski French Studies Bersani, Leo and Ulysse Dutoit. Arts of Impoverishment: Beckett, Rothko, Resnais by Thomas Trezise Boldt-Irons, Leslie Anne. On Bataille: Critical Essays by Walter A. Strauss Deleuze, Gilles. Negotiations. Trans. Martin Joughin by Charles J. Stivale Fisher, Dominique D. Staging of Language and Language(s) of the Stage: Mallarmé's poëme critique and Artaud's poetry-minus-text by Maryse Fauvel Goodall, Jane. Artaud and the Gnostic Drama by Claudine G. Fisher Lydon, Mary. Skirting the Issue: Essays in Literary Theory by Carol J. Murphy German Studies Barnouw, Dagmar. Critical Realism: History, Photography, and the Work of Siegfried Kracauer by Florence Martin Pfandl-Buchegger, Ingrid. David Lodge als Literaturkritiker, Theoretiker and Romanautor by Charles A. Grair Samuels, Clarise. Holocaust Visions: Surrealism and Existentialism in the Poetry of Paul Celan by Francis Michael Sharp Stefan, Verena. Shedding and Literally Dreaming. Shedding. Trans. Johanna Steigleder Moore and Beth E. Weckmueller; Literally Dreaming. Trans. Johanna Albert and Tobe Levin; "Euphoria and Cacophony." Trans. and Afterword Tobe Levin by Miriam Frank Stern, J.P. The Dear Purchase: A Theme in German Modernism by Theodore Ziolkowski Russian Studies Berry, Ellen E. and Anesa Miller-Pogacer, eds. Re-Entering the Sign: Articulating New Russian Culture by Rolf Hellebust Erlich, Victor. Modernism and Revolution: Russian Literature in Transition by Henry Elbaum Hohne, Karen and Helen Wussow, eds. A Dialogue of Voices: Feminist Literary Theory and Bakhtin by Laura Beraha Masing-Delic, Irene. Abolishing Death: A Salvation Myth of Russian Twentieth-Century Literature by Rolf Hellebust Paperno, Irina and Joan Delaney Grossman, eds. Creating Life: The Aesthetic Utopia of Russian Modernism by Constantin V. Ponomareff Spanish Studies Cardenal, Ernesto. The Doubtful Strait. Trans. John Lyons by Juan Carlos Galeano Garcia Marquez, Gabriel. Of Love and Other Demons by John Cussen Lindstrom, Naomi. Twentieth-Century Spanish American Fiction by Norma Helsper Meyer, Doris, Ed. Reinterpreting the Spanish American Essay: Women Writers of the 19th and 20th Centuries by Judy Maloof and Fernando Unzueta Nantell, Judith. The Poetry of Francisco Brines: The Deconstructive Effects of Languages by Anita M. Hart Taylor, Diana and Juan Villegas, Eds. Negotiating Performance: Gender, Sexuality, & Theatricality in Latin America by Anne M. Pasero
Keywords: Verena Andermatt Conley; Rethinking Technologies; Laurence M. Porter; Vincent B. Leitch; Cultural Criticism Literary Theory Poststructuralism; Merry M. Pawlowski; Leo Bersani; Ulysse Dutoit. Arts of Impoverishment: Beckett Rothko Resnais; Thomas Trezise; Leslie Anne Boldt-Irons; On Bataille: Critical Essays; Walter A. Strauss; Gilles Deleuze; Negotiations; Martin Joughin; Charles J. Stivale; Dominique D. Fisher; Staging of Language and Language(s) of the Stage: Mallarmé' s poëme critique and Artaud' s poetry-minus-text; Maryse Fauvel; Jane Goodall; Artaud and the Gnostic Drama; Claudine G. Fisher; Mary Lydon; Skirting the Issue: Essays in Literary Theory; Carol J. Murphy; Dagmar Barnouw; Critical Realism: History Photography and the Work of Siegfried Kracauer; Florence Martin; Ingrid Pfandl-Buchegger; David Lodge als Literaturkritiker Theoretiker and Romanautor; Charles A. Grair; Clarise Samuels; Holocaust Visions: Surrealism and Existentialism in the Poetry of Paul Celan; Francis Michael Sharp; Verena Stefan; Shedding and Literally Dreaming; Shedding; Johanna Steigleder Moore; Beth E. Weckmueller; Literally Dreaming; Johanna Albert; Euphoria and Cacophony; Tobe Levin; Miriam Frank; J.P. Stern; The Dear Purchase: A Theme in German Modernism; Theodore Ziolkowski; Ellen E. Berry; Anesa Miller-Pogacer; Re-Entering the Sign: Articulating New Russian Culture by Rolf Hellebust; Victor Erlich; Modernism and Revolution: Russian Literature in Transition; Henry Elbaum; Karen Hohne; Helen Wussow; A Dialogue of Voices: Feminist Literary Theory and Bakhtin; Laura Beraha; Irene Masing-Delic; Abolishing Death: A Salvation Myth of Russian Twentieth-Century Literature; Rolf Hellebust; Irina Paperno; Joan Delaney Grossman; Creating Life: The Aesthetic Utopia of Russian Modernism; Constantin V. Ponomareff; Ernesto Cardenal; The Doubtful Strait; John Lyons; Juan Carlos Galeano; Gabriel Garcia Marquez; Of Love and Other Demons; John Cussen; Naomi Lindstrom; Twentieth-Century Spanish American Fiction; Norma Helsper; Doris Meyer; Reinterpreting the Spanish American Essay: Women Writers of the 19th and 20th Centuries; Judy Maloof; Fernando Unzueta; Judith Nantell; The Poetry of Francisco Brines: The Deconstructive Effects of Languages; Anita M. Hart; Diana Taylor; Juan Villegas; Negotiating Performance: Gender Sexuality & Theatricality in Latin America; Anne M. Pasero